Solid supported hmimTf2N for CO2 adsorption - Md Nurul, S. (2014)
Ionic liquids are new alternative solvents that can be used to separate carbon dioxide in the gas separation process. However, the high viscosity of ionic liquids limits the mass transfer of solutes into ionic liquids. In this work, 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide (hmimTf2N) was impregnated onto porous Al2O3 and SiO2 and tested for CO2 adsorption at pressure up to 40 bar at 25Â°C. The screening process showed that hmimTf2N-Si gave higher CO2 adsorption capacity compared to hmimTf2N-Al and pure hmimTf2N. The experimental work was further investigated by varying the composition of hmimTf2N inside SiO2 pores. The composition of hmimTf2N was varied from 10 wt% to 40 wt%. The result showed the 10 wt% composition gave the highest CO2 adsorption compared to 20 wt%, 30 wt% and 40 wt%. The lower CO2 adsorption by 20 wt%, 30 wt% and 40 wt% might be due to the blockage of SiO2 pores by excess hmimTf2N. From this research, it proved that porous solid support can provide high surface area that is necessary to accommodate intimate contact between CO2 and solid supported ionic liquid and increases the CO2 adsorption capacity. Â© (2014) Trans Tech Publications, Switzerland.